Prevalence and Genetic Diversity of Enterococcus faecalis Isolates from Mineral Water and Spring Water in China - Wei, Lei; Wu, Qingping; Zhang, Jumei; Guo, Weipeng; Chen, Moutong; Xue, Liang; Wang, Juan; Ma, Lianying (Frontiers in Microbiology, 2017)
Enterococcus faecalis is an important opportunistic pathogen which is frequently detected in mineral water and spring water for human consumption and causes human urinary tract infections, endocarditis and neonatal sepsis. The aim of this study was to determine the prevalence, virulence genes, antimicrobial resistance and genetic diversity of E. faecalis from mineral water and spring water in China. Of 314 water samples collected from January 2013 to January 2014, 48 samples (15.3%) were contaminated E. faecalis. The highest contamination rate occurred in activated carbon filtered water of spring water (34.5%), followed by source water of spring water (32.3%) and source water of mineral water (6.4%). The virulence gene test of 58 E. faecalis isolates showed that the detection rates of asa1, ace, cylA, gelE and hyl were 79.3%, 39.7%, 0%, 100%, 0% respectively. All 58 E. faecalis isolates were not resistant to 12 kinds of antibiotics (penicillin, ampicillin, linezolid, quinupristin / dalfopristin, vancomycin, gentamicin, streptomycin, ciprofloxacin, levofloxacin, norfloxacin, nitrofurantoin, tetracycline). Enterobacterial repetitive intergenic consensus-PCR classified 58 isolates and three reference strains into nine cluters with a similarity of 75%. This study is the first to investigate the prevalence of E. faecalis in mineral water and spring water in China. The results of this study suggested that spring water could be potential vehicles for transmission of E. faecalis.